PENGARUH KONSELING TERHADAP TINGKAT KECEMASAN SEBELUM PROSES PERSALINAN PADA WANITA HAMIL TRIMESTER KETIGA - Sulistyo Dewi Wahyu Rini; Vira Amelia; Nanang Muhibuddin; Hanifuddin Dwi Satria (Poltekkes Kemenkes Maluku, 2026)
Anxiety during pregnancy can be triggered by limited knowledge, which gives rise to fear of childbirth, feelings of anxiety, sadness, stress, and even depression, thus increasing the psychological burden on pregnant women. Counseling should be an important part of antenatal care. The purpose of this study was to analyze the effect of counseling regarding the childbirth process on the level of anxiety before childbirth in the third trimester of pregnant women in the Bendo Community Health Center, Kediri Regency. This study used a pre-experimental design with a population of all third trimester pregnant women in the Bendo Community Health Center, Kediri Regency (n=37). A sample of 16 respondents was selected using a purposive sampling method. HARS and ZSAS-based questionnaires were used to collect data, and the Wilcoxon Signed Rank test was used for analysis. The results showed that before the counseling, most respondents (81.25%) were at a moderate level of anxiety, while after the counseling, the majority of respondents (81.25%) experienced mild anxiety. The Wilcoxon test showed a p-value <α (0.001 <0.05). The analysis shows that counseling on the childbirth process has an impact on the level of anxiety before delivery among pregnant women in their third trimester in the Bendo Community Health Center, Kediri Regency. It is hoped that research sites will use these results as an overview and input for improving midwifery services.